Impact of Economic Inequality on the Probability of Revolutionary Events: The World Experience from 1995 to 2021 - Ustyuzhanin, Vadim; Fain, Egor; Korotaev, Andrey (Journal of Economic Sociology, 2025)
The article tests several hypotheses about the impact of wealth and income inequality, as well as inequality in human capital, on the risks of armed and unarmed revolutions. Using the revolutionary destabilization database from the Center for Stability and Risk Analysis (CSRA) at HSE University, along with data collected by Mark Beissinger, the study analyzes most countries worldwide from 1995 to 2021 and tests several hypotheses. The study has shown that income inequality—particularly wealth inequality— has a curvilinear inverted U-shaped relationship with the likelihood of both unarmed and armed revolutionary uprisings. The likelihood of revolutionary uprisings increases as income inequality (especially wealth inequality) rises, but only up to a certain level; further increases in such inequality lead to the elite concentrating a disproportionately high share of resources, enabling them to maintain power by using these resources to suppress opposition and/or coopt part of it. In the case of unarmed revolutions, this dependence is observed only for wealth inequality, while income inequality does not demonstrate a significant correlation with the probability of unarmed revolutionary uprisings. Conversely, for armed revolutions, the described relationship is evident for both wealth and income inequality. When considering inequality in access to education and healthcare—critical components of human capital growth—the risks of revolutionary destabilization for elites, driven by the hyperconcentration of consumption of these services in their hands, continue to grow with increasing inequality, regardless of how high it reaches. However, the benefits of this hyperconcentration are not straightforward, as it does not allow for co-optation and suppression of discontented individuals in the same manner as the concentration of wealth or income does. Consequently, any increase in inequality in access to education and healthcare—regardless of its magnitude—has a destabilizing effect, raising the likelihood of both armed and unarmed revolutionary uprisings.